Специфіка смисложиттєвих орієнтацій жінок, які реалізують патерналістські установки в економічній поведінці - Штриголь, Д. В.; Shtrygol, D. V.; ORCID: http://orcid.org/0000-0001-7346-2677; Ламаш, І. В.; Lamash, I. V.; ORCID: http://orcid.org/0000-0002-9548-4006; ResearcherID: I-7320-2016 (Право і Безпека. - 2016. - № 2. - С. 156-160, 2016)
Викладено результати теоретичного й емпіричного дослідження смисложиттєвих орієнтацій жінок, які реалізують патерналістські установки в економічній поведінці. Установки на економічний патерналізм відображають сподівання на державу у важких економічних обставинах, очікування від неї різного виду допомоги, що заохочує пасивність та ухилення від особистої моральної відповідальності. Надання психологічної допомоги таким особам може бути ефективним лише за умови врахування їх психологічних особливостей. Установлено, що для таких жінок характерними є менша осмисленість цілей у майбутньому та більш низька задоволеність своїм теперішнім життя. Вони вбачають певні межі своєї здатності до контролю, самостійного прийняття рішень та активної діяльності, спрямованої на перспективу, що обумовлює зниження загального показника усвідомленості життя.

The authors of the article have provided the results of theoretical and empirical studies of purport orientations of women realizing paternalistic installations within economic conduct. Installations on economic paternalism reflect hope for the state in difficult economic circumstances, expectations from it various types of assistance that encourages passivity and evasion of personal moral responsibility. Studying psychological characteristics of women who realize the paternalistic installations, with rather active development of certain problems of economic consciousness and conduct, acquires relevance in today’s realities. The study involved 72 women aged 28–40 years who were divided into 2 groups. The first group – of 32 women who do not work and do not carry out attempts on employment, use social services to solve various life problems – has been defined by us as a group of women who realize paternalistic installations within economic conduct. The second group consisted of 40 working women who have never applied for assistance in social services. Women who realize paternalistic installations within economic conduct, comprehend to a lesser extent the future objectives, are less focused, their life is more focused on the past or present day. They feel less satisfaction with their current life; less likely to believe in themselves, the ability to control the events of their lives; see certain limits of their ability to control, independent decision-making and activism aimed at the future, hence the decrease in the overall rate of awareness of life. The obtained results may be used for the differentiation of prevention and psycho-correctional work.

Изложены результаты теоретического и эмпирического исследования смысложизненных ориентаций женщин, которые реализуют патерналистские установки в экономическом поведении. Установки на экономический патернализм отражают надежды на государство в тяжелых экономических обстоятельствах, ожидание от него разного рода помощи, что поощряет пассивность и уклонение от личной моральной ответственности. Осуществление психологической помощи таким лицам может быть эффективными только при условии учёта их психологических особенностей. Установлено, что для таких женщин характерна меньшая осмысленность целей в будущем и более низкая удовлетворенность своей нынешней жизнью. Они видят определённые пределы своей способности к контролю, самостоятельному принятию решений и активной деятельности, направленной на перспективу, что обусловливает снижение общего показателя осознанности жизни.
Specificity of purport orientations of women realizing paternalistic installations within economic conduct
Специфика смысложизненных ориентаций женщин, которые реализуют патерналистские установки в экономическом поведении
Штриголь, Д. В. Специфіка смисложиттєвих орієнтацій жінок, які реалізують патерналістські установки в економічній поведінці / Д. В. Штриголь, І. В. Ламаш // Право і Безпека. - 2016. - № 2. - С. 156-160.
Штриголь Д. В., Ламаш І. В. "Специфіка смисложиттєвих орієнтацій жінок, які реалізують патерналістські установки в економічній поведінці." Право і Безпека 2 (2016): 156-160.
Shtryhol, D.V. and Lamash I.V. (2016) “Specificity of purport orientations of women realizing paternalistic installations within economic conduct” [“Spetsyfika smyslozhyttievykh oriientatsii zhinok, yaki realizuiut paternalistski ustanovky v ekonomichnii povedintsi”], Pravo i Bezpeka, No. 2, pp. 156–160.
Keywords: Психологія. Рsychology. Психология; Наукові публікації. Scientific publications. Научные публикации; жінка; економічна поведінка; економічний патерналізм; патерналістські установки; смисложиттєві орієнтації; economic conduct; woman; economic paternalism; paternalistic installation; life purport orientations; женщина; смысложизненные ориентации; установки; экономический патернализм; экономическое поведение